First-Line Immunotherapy for Non–Small-Cell Lung Cancer. Issue 6 (20th February 2022) - Reck, Martin; Remon, Jordi; Hellmann, Matthew D.
Abstract : For patients with metastatic non–small-cell lung cancer (mNSCLC), the last decade has been characterized by critical progress that has contributed to substantially improved survival. In particular, the development of specific antibodies against the programmed death (PD-1) receptor, programmed death-ligand 1 (PD-L1), and the cytotoxic T-lymphocyte–associated protein 4 receptor in the therapeutic strategy of mNSCLC either in first- or in second-line settings have led to unprecedented prolonged survival for a proportion of these patients. Although clinical development of immune checkpoint inhibitors with anti–PD-1 and PD-L1 therapies largely began as monotherapy in the second-line setting, the more recent progress has shifted toward combination approaches in first-line settings as well as the integration of immunotherapy into the clinical paradigm in earlier stages. Today, with the exception of mNSCLC harboring targetable oncogenes, nearly all patients with mNSCLC receive PD-1 or PD-L1 therapy in first-line settings. Here we report the current status of first-line immunotherapy in mNSCLC together with current challenges in selecting the best immunotherapeutic approach for the individual patient.